HUBUNGAN FAKTOR LINGKUNGAN DAN POLA ASUH IBU TERHADAP KEJADIAN STUNTING DI KENAGARIAN BALINGKA - Yuliza Anggraini; Marisa Amalia (Ensiklopedia of Journal, 2023)
Stunting is low height for age which is characterized by delayed growth in children which results in failure to achieve normal height for age. the incidence of stunting in West Sumatra is still high at 15.1% in 2021. Balingka district is one of the districts in Agam district which has a fairly high prevalence of stunting. Many factors that are interrelated with each other are the causes of stunting, one of which is environmental factors and maternal parenting. The aim is to determine the relationship between environmental factors and maternal parenting patterns with the incidence of stunting in Kenagarian Balingka. The method uses a cross sectional design. Sampling by simple random sampling with a total sample of 55 toddlers aged 12-59 months. The results showed that there was no significant relationship between environmental factors in the form of environmental sanitation factors and the incidence of stunting in Balingka district (p value 0.655), there was no relationship between personal hygiene and stunting in Balingka district (p value 0.408), there was no relationship between exclusive breastfeeding with the incidence of stunting in Kenagarian Balingka (p value 0.170) and there is no relationship between the provision of complementary foods and the incidence of stunting in Kenagarian Balingka (p value 0.102). The conclusion is that there is no relationship between environmental factors and mother's upbringing with the incidence of stunting in Kenagarian Balingka.